Influence of Drying Phases in a Continuous Flooded Situation on Liberation of Different Forms of Inorganic and Organic N in Soil - Saha, Dipankar; Paul, Niladri; Das, Arunava (International Journal of Bio-resource and Stress Management, 2023)
Nitrogen is one of the major nutrients required for plant growth and metabolic activities. The efficient use of N depends on different transformation processes-mineralization and immobilization, in soil. The present investigation was conducted with a view to know the release pattern of different forms of inorganic and organic N in soil maintained under waterlogged situation but subjected to one or two drying phases. Results revealed that irrespective of soils, cropping and stages of plant growth as well as phases of drying and submergence, the amount of native exchangeable NH4+decreased over 0th day of plant growth. Maintenance of a drying phase either at pre-tillering or at pre-flowering stage of rice showed an accumulation of higher amount of exchangeable NH4+, where as comparatively lower amount of NO3- -N is registered over the continuous flooded situation. This decrease of soluble NO3- -N was more in pre-flowering than pre-tillering stage of rice. Again, irrespective of soils, cropping and drying phases, the amount of hydrolysable NH4+and amino acid-N increased at pre-tillering but decreased at pre-flowering stage when the soils are subjected to drying phase at both the stages of crop growth. Addition of inorganic N has no drastic influence on accumulation of hydrolysable organic NH4+and amino acid-N in waterlogged soils. Maintenance of a drying phase either at pre-tillering or at pre-flowering stage favours consumption of higher amount of N from the soil system at the maturity stage of rice. This trend of results is also observed in N fertilized soil.